Pengaruh Pendidikan Islam Dalam Keluarga Dan Budaya Religius Sekolah Terhadap Kecerdasan Spiritual Siswa di MIN 3 Ponorogo - Anitasari, Lia; Murdianto, Murdianto; Fikriawan, Suad (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2024)
The purpose of the study was to determine the influence of Islamic education in the family and religious culture of the school on the spiritual intelligence of students at MIN 3 Ponorogo. This study was conducted at MIN 3 Ponorogo using quantitative research methods and the research design was correlation research. The population in this study were 217 students in grades 4-6. The sampling technique was random sampling. The researcher took a sample of 54 people as respondents. Data analysis used multiple regression analysis, t-test, F-test with a quantitative approach. The results of the study concluded that Islamic education in the family and religious culture of the school had a very strong influence, both partially and simultaneously on the spiritual intelligence of students at MIN 3 Ponorogo. While the simultaneous contribution or contribution of the variables of Islamic education in the family and religious culture of the school to the spiritual intelligence of students at MIN 3 Ponorogo was 99% and 1% was influenced by other variables.